(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2015)
TheÂ architectural order,Â the analogic transfigurationÂ ofÂ theÂ petrifaction process, representsÂ the unchangingÂ tectonic-expressiveÂ icon, resulting from the material and constructive variability of the architecture; a variability today more andÂ moreÂ subject to the spectacularÂ advancedÂ visualÂ technologiesÂ orÂ to those languages based on the predominant, often misrepresenting, sensorial action. In apparent contrast to these tendencies are those looking for possible new codes, able to respond to the chaotic condition of Babel, that characterizes the contemporary city, experiencing actions aimed at combining the update of the constructive and linguistic codes, with the phenomena induced by a different perception of the architectural landscape. To these theories belong all those trends of research, involved in architecture and the arts, according to a basically pseudoscopic approach; the same that, from Greeks onwards, is the privileged place of narrative function of the building. The domain most concernedÂ byÂ this experimentation,Â thatÂ is deliveredÂ toÂ our future, is, of course, the tectonic one of theÂ relationship between point elements,Â such asÂ columns,Â pillarsÂ and frames. These elements,Â declinedÂ inÂ overlapping, simultaneous orÂ diachronic intersections,Â may try toÂ composeÂ new potentialÂ orders,Â new potentialÂ rhythmicÂ sequencesÂ capable ofÂ expressingÂ in harmonic phenomena the current almostÂ incomprehensibleÂ shapes ofÂ our citiesÂ andÂ landscapes. Â